Religiosity and Death Anxiety: A Study of Muslim Dars Attendees - Saleem, Tamkeen (Journal of religion and health, 2020)
Dars is usually considered a religious lecture or activity where attendees spend much time in search of Islamic information, which often keeps the attendees away from negative thinking. Religious directions, belief salience, spiritual activities and practices are significant assets for dealing with difficult situations and odds of life. Death anxiety can increase the vulnerability of development of any psychological illness. Therefore, it is vital to study whether religiosity can serve as a buffering agent to death anxiety. The objective of our study was to examine the relationship between religiosity and death anxiety among Muslim dars attendees. We also aimed to investigate the gender-based differences in religiosity and death anxiety among Muslim dars attendees. A purposive sample of 200 adults (male n?=?100 and female n?=?100) with the age range of 20-60 years participated in the present study. The sample was collected from informal religious gatherings (dars) from Islamabad and Rawalpindi. The information was gathered through self-reporting questionnaires, death anxiety scale and index of religiosity. The questionnaires were in Urdu (native language) for ease and convenience of the respondents. Variable correlation analysis and t test was applied statistically through SPSS 21 version. The findings of the study indicate that there is a significant negative relationship between religiosity and death anxiety. Results also revealed that there is insignificant difference in religiosity between male and female Muslim adults. Results also specified that the level of death anxiety is higher in female than in male Muslim adults. Religiosity has a significant inverse relationship with death anxiety, and this can be helpful in reducing the anxiety-related features. Being a trans-diagnostic construct, measures can be taken to control death anxiety in order to enhance the mental well-being of masses. The present research also puts forward that the development of religious beliefs and interventions can help people to better adjust in life.